Do Pre-Registration and Pre-Analysis Plans Reduce p-Hacking and Publication Bias?: Evidence from 15,992 Test Statistics and Suggestions for Improvement - Abel Brodeur; Nikolai M. Cook; Jonathan S. Hartley; Anthony Heyes (Global Labor Organization (GLO), 2023)
Pre-registration is regarded as an important contributor to research credibility. We investigate this by analyzing the pattern of test statistics from the universe of randomized controlled trials (RCT) studies published in 15 leading economics journals. We draw two conclusions: (a) Pre-registration frequently does not involve a pre-analysis plan (PAP), or sufficient detail to constrain meaningfully the actions and decisions of researchers after data is collected. Consistent with this, we find no evidence that pre-registration in itself reduces p-hacking and publication bias. (b) When pre-registration is accompanied by a PAP we find evidence consistent with both reduced phacking and publication bias.
Keywords: B41; C13; C40; C93; 330; Pre-analysis plan; Pre-registration; p-Hacking; Publication; bias; Research credibility